1998
DOI: 10.1099/0022-1317-79-8-1989
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the UL55 gene product of herpes simplex virus type 2.

Abstract: We have identified the herpes simplex virus type 2 (HSV-2) UL55 gene product using a rabbit polyclonal antiserum raised against a recombinant 6iHis-UL55 fusion protein expressed in Escherichia coli. The antiserum reacted specifically with a 23 kDa protein in HSV-2 186-infected cell lysates. The protein was not detectable in the presence of the viral DNA synthesis inhibitor phosphonoacetic acid. Indirect immunofluorescence studies localized the UL55 protein within and at the periphery of the nucleus as discrete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 13 publications
1
24
0
Order By: Relevance
“…Hence, U L 7 was found in HSV-2 virions (70), while U L 23 was detected in KHSV and alcelaphine herpesvirus-1 virions (21,111). In contrast, U L 55 is seemingly absent from mature HSV-2 (103). The current report clearly shows that all four proteins constitute novel components of the virions.…”
Section: Discussionmentioning
confidence: 59%
“…Hence, U L 7 was found in HSV-2 virions (70), while U L 23 was detected in KHSV and alcelaphine herpesvirus-1 virions (21,111). In contrast, U L 55 is seemingly absent from mature HSV-2 (103). The current report clearly shows that all four proteins constitute novel components of the virions.…”
Section: Discussionmentioning
confidence: 59%
“…Thus, some laboratories clearly demonstrated that UL34 and UL31 were detected only at the nuclear membrane in HSV-1-infected cells and in cells cotransfected with a UL34-and UL31-expressing plasmid (61,62,65). In contrast, the others, including this laboratory, reported nucleoplasmic localization of UL34 and/or UL31, in addition to nuclear membrane localization, in cells infected with HSV-1 or HSV-2 and in cells transiently coexpressing UL31 and UL34 (8,66,67,73,74). Furthermore, the nucleoplasmic distribution of pseudorabies virus UL31 and UL34 homologues in infected cells has also been reported (19).…”
Section: Discussionmentioning
confidence: 89%
“…Bound primary antibodies were detected using horseradish peroxidase-linked sheep anti-rabbit immunoglobulin G (IgG) (Amersham) and ECL Western blotting detection reagents (Amersham). The specific antiserum for the UL31 protein was described previously (Yamada et al, 1998).…”
Section: Generation Of Polyclonal Antisera In Rabbitsmentioning
confidence: 99%
“…Plasmid pET28-US2 was transformed into E. coli strain BL21(DE3) (Novagen) which, following induction with IPTG, expressed large quantities of 6iHis-US2 fusion protein. Purification of the US2 fusion protein and immunization were done as described previously (Yamada et al, 1998). Both preimmune and immune antisera were extensively adsorbed against acetone powder of E. coli strain BL21(DE3) and uninfected Vero cells prior to use, as described by Harlow & Lane (1988).…”
Section: Generation Of Polyclonal Antisera In Rabbitsmentioning
confidence: 99%
See 1 more Smart Citation